Motif-Based Graph Attentional Neural Network for Web Service Recommendation - Wang, Guiling; Yu, Jian; Nguyen, Mo; Zhang, Yuqi; Yongchareon, Sira; Han, Yanbo (Elsevier BV, 2023)
Deep Neural Networks (DNN) based collaborative filtering has been successful in recommending services by effectively generalizing graph-structured data. However, most existing approaches focus on first-order interactions. Although recent approaches have utilized high-order connectivity, they still limit themselves to simple interactions and ignore the pattern of structural sub-graphs/motifs. In this study, we first explore the commonly used motifs in the Mashup-API interaction bipartite graph and propose a dedicated algorithm to generate the motif adjacency matrix. We then propose a Motif-based Graph Attention Network for service recommendation (MGSR) that utilizes a motif-based attention mechanism to capture the high-order information of various motifs, and a Collaborative Filtering model to generate the recommendation prediction. We have conducted extensive experiments on ProgrammableWeb dataset and our results demonstrate the superior performance of our proposed framework over some state-of-the-art approaches.
Keywords: 46 Information and Computing Sciences; 4611 Machine Learning; Neurosciences; Networking and Information Technology R&D (NITRD); 08 Information and Computing Sciences; 15 Commerce, Management, Tourism and Services; 17 Psychology and Cognitive Sciences; Artificial Intelligence & Image Processing; 4602 Artificial intelligence; 4605 Data management and data science; 4611 Machine learning